CHALLENGES AND SOLUTIONS FOR DIGITAL TRANSFORMATION OF SMEs: A HUMAN RESOURCE DEVELOPMENT PERSPECTIVE - Dewi Puspaningtyas Faeni; Ramdhan Wibisana (Draf Solusi Indonesia, 2024)
This paper explores the challenges and solutions related to the digital transformation of Small and Medium Enterprises (SMEs) from a Human Resource Development (HRD) perspective. SMEs often face hurdles such as limited digital skills among employees, resistance to change, and financial constraints. To overcome these challenges, effective HRD strategies are essential, including investments in upskilling, change management initiatives, and strategic partnerships. By enhancing employees' technical capabilities and fostering a culture of adaptability, SMEs can successfully integrate digital technologies into their operations. Collaborations with external stakeholders further enable SMEs to access resources needed for digital transformation, enhancing their competitiveness and sustainability in today's digital economy.